If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-8x=6(7x+)-3(2+7x)
We move all terms to the left:
6x-8x-(6(7x+)-3(2+7x))=0
We add all the numbers together, and all the variables
6x-8x-(6(+7x)-3(7x+2))=0
We add all the numbers together, and all the variables
-2x-(6(+7x)-3(7x+2))=0
We calculate terms in parentheses: -(6(+7x)-3(7x+2)), so:We get rid of parentheses
6(+7x)-3(7x+2)
We multiply parentheses
42x-21x-6
We add all the numbers together, and all the variables
21x-6
Back to the equation:
-(21x-6)
-2x-21x+6=0
We add all the numbers together, and all the variables
-23x+6=0
We move all terms containing x to the left, all other terms to the right
-23x=-6
x=-6/-23
x=6/23
| 3x-11x=152x | | 2(1+2b)+6(b+5)=b-8+1+6b | | 14/7=k/8 | | 6u+4(u+8)=34 | | -6u+4(u+8)=33 | | 2(1+2b)+6(b+5=b-8+1+6b | | 3x+30=12x | | 1y-8y+56=2 | | 75+x/5=79 | | 2(6-7p)+2(p-7)=-38 | | 3s+9=1s-4 | | m÷5+6=9 | | 5(-x+5)-6(x-3)=-34 | | (24p-66)/3=3p+43 | | 9/11y=3/7 | | -20=x+16 | | 11/12=2/4h | | (1/3)(24p-66)=3p+43 | | x/2+x/5=2.1 | | |3x-21|=0 | | 1-8x=5(-x-5)+5 | | 24+6x=-6+6(x+6) | | -5(3x-17)=2(x-15)-55 | | 1x-13=7x-19 | | n3−5=12 | | -10-2y=30 | | 2n+20=5(6n+4) | | 18+4x=5(-x+2)-37 | | 2n+20=(6n+4) | | 4(c+6)-2c=-1 | | 6x+29=203 | | 4x+29=148 |